2018
DOI: 10.1111/rda.13273
|View full text |Cite
|
Sign up to set email alerts
|

S100 calcium‐binding protein A12 as a diagnostic index for subclinical mastitis in cows

Abstract: Diagnosis of subclinical mastitis is very important in management of the dairy industry and improvement of dairy cow productivity. S100A12, that is found in related tissues of mammals, is considered as an index for diagnosing inflammatory reaction. To evaluate whether S100A12 is involved in subclinical mastitis, milk somatic cell mRNA from 276 dairy cows was used to detect the transcriptional level of S100A12 by real-time quantitative polymerase chain reaction. A predictive analysis for mastitis was performed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It recruits leukocytes, elevates cytokines and chemokines, and controls leukocyte adhesion and migration [ 73 ]. In cows, S100A12 is a marker for inflammatory responses and subclinical mastitis [ 74 ]. The upregulation of LBP, PTX3, and S100A12 in multiple tissues suggests that NEB influences systemic inflammation, and these three genes may serve as diagnostic indicators of systemic inflammation caused by NEB.CXCL2 regulates and inflames inflammation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It recruits leukocytes, elevates cytokines and chemokines, and controls leukocyte adhesion and migration [ 73 ]. In cows, S100A12 is a marker for inflammatory responses and subclinical mastitis [ 74 ]. The upregulation of LBP, PTX3, and S100A12 in multiple tissues suggests that NEB influences systemic inflammation, and these three genes may serve as diagnostic indicators of systemic inflammation caused by NEB.CXCL2 regulates and inflames inflammation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 can bind to CXCR1 and CXCR2 receptors with high a nity, and as the primary chemokine of neutrophils, it plays a vital role in the initiation and maintenance of in ammatory response [39]. S100A12 found in mammalian tissues is considered to be an indicator for the diagnosis of in ammatory responses [40]. S100A12 is associated with innate immune responses and is mainly expressed in neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical hypocalcemia impairs the metabolic and physiological responses that regulate the welfare and productivity of transitional dairy cows (Rodrigues et al, 2020). Calcium mineral is crucial in numerous structural and biochemical processes in udder defense mechanisms, including the contractile activity of the teat sphincter (Paulrud, 2005;Mahjoubi et al, 2017), immune cell functions (Kimura et al, 2006;Zhang et al, 2019), blood coagulation (Libera et al, 2021), and teat canal keratin formation and S100 calcium-binding protein functions (Smolenski et al, 2015;Zhong et al, 2018). Histomorphological studies have shown that the teat canal returns to its original state after milking with the contraction of exible, smooth muscle cells surrounding the teat canal (Giesecke et al, 1972;Van Der Merwe, 1985;Paulrud, 2005).…”
Section: Introductionmentioning
confidence: 99%